Fashion, Identity, Image - Jobling, Paul; Nesbitt, Philippa; Wong, Angelene (Bloomsbury Visual Arts, 2022)
How has the fashion industry responded to turn-of-the-millennium non-binary identities? Do they have a supportive or exploitative relationship with queer, trans and ageing subjects? Fashion, Identity, Image unpacks these questions and many more in relation to clothing and representation, identity and body politics in British, European and American culture between 1990 and 2020. Jobling, Nesbitt and Wong explore issues of intersectionality and inclusivity through groundbreaking shows, including Maria Grazia Chiuris We Should All Be Feminists catwalk show for Dior (Spring-Summer 2017), Alexander McQueens The Widows of Culloden collection (Fall-Winter 2006), and the role of transgender models such as Oslo Grace since 2015. Looking to the future of our relationship with fashion, theres also an investigation of the android as a redemptive figure in Alessandro Micheles cross-cultural cyborg collection for Gucci (Autumn-Winter 2018/2019) and the impact of the ageing population with analysis of age and memory in work such as Magali Nougarèdes Crossing the Line (2002), and pleasure and morality in fashion publicity since the 1990s for the likes of Calvin Klein, DandG and American Apparel
Includes bibliographical references
1. Authoring Fashion, Intersecting Sex and Gender: Introduction; Maria Grazia Chiuris We Should All Be Feminists T-Shirt for Christian Dior: Branding, identity and authorship; Between the womb and the gay parade: Alexander McQueens The Widows of Culloden as poetic text; Subverting the symbolic order: McQueens abject woman; Conclusion: Squaring up to the phallic mother; Notes --2. Written on the body: Fashion, clothing and age: Introduction; Active ageing, youthfulness and fashion; Fashion For All Ages and the new old model army; Race and reversing convention; Conclusion: From idiotic methods to the realities of time and place; Notes --3. (Un)Gendering the runway: Introduction; Forerunners of transgender and non-binary identities in fashion; The advent of transgendered models; The abject trans-model; Between abjection and acceptance; Come into the (trans)garden: The heterotopia of fashion; The authentic self; Other models: Intersectionality and wider diversity in the fashion industry; Tokenism versus activism; Conclusion: Between tokenism and authenticity; Notes --4. Loving the alien: Fashion and cyborg identities: Introduction; Andrea Giacobbe and Simplex Concordia; Alessandro Michele and the Gucci Cyborg; Compromising race and diversity; A genuine cyborg manifesto?; Conclusion: Towards emancipatory possibilities; Notes --Epilogue
Keywords: Geschichte 1990-2020; Fashion design & theory / bicssc; Fashion -- Social aspects -- Western countries -- Case studies; Fashion -- Politcal aspects -- Western countries -- Case studies; Body image -- Western countries -- Case studies; Körperbild; Mode; Identität; Europa; USA